Effect of propolis mouthwash on the incidence of ventilator-associated pneumonia in intensive care unit patients: a comparative randomized triple-blind clinical trial - Nayereh Darbanian; Monir Nobahar; Raheb Ghorbani (BMC, 2024)
Abstract Objectives Ventilator-associated pneumonia (VAP) increases the length of hospitalization and mortality rate. This study aimed to determine the effect of propolis mouthwash on the incidence of VAP in intensive care unit (ICU) patients. Materials and methods Triple-blind, comparative randomized, controlled clinical trial was conducted over one year, with 110 ICU patients at Imam-Hossein and Bahar hospitals (Shahroud) and Kowsar Hospital (Semnan) in Iran. The intervention group used 15 cc of 0.06% propolis mouthwash solution twice daily at 8 AM and 4 PM for seven days. The control group used 15 cc of 0.2% chlorhexidine mouthwash at the same times and duration. Data were collected using a demographic questionnaire, APACHE II, Beck Oral Assessment Scale, and Modified Clinical Pulmonary Infection Score (MCPIS). Results There was no significant difference in demographic information, disease severity, and oral health between the two groups before and after intervention (P > 0.05). The incidence of VAP in the intervention group compared to the control group was 10.9% vs. 30.9% on the third day (P = 0.0166, 95% CI: 0.53-0.83 and RR = 0.35), 23.6% vs. 43.6% on the fifth day (P = 0.0325 and 95% CI: 0.31-0.95 and RR = 0.54), and 25.5% vs. 47.3% on the seventh day (P = 0.0224, 95% CI: 0.32-0.92, and RR = 0.54). The Mann-Whitney indicated the incidence of VAP was significantly lower in the intervention group on the third, fifth, and seventh days. Conclusion Propolis mouthwash can be considered as an alternative to chlorhexidine mouthwash for ICU patients. Clinical relevance Propolis mouthwash serves as a simple, economical intervention to potentially reduce incidence of VAP. Trial registration (IRCT20110427006318N12, date 02.04.2019).